Dopamine stimulation of postnatal murine subventricular zone neurogenesis via the D3 receptor. - Kim, Y; Wang, W; Comte, I; Pastrana, E; Tran, P; Brown, J; Miller, R; Doetsch, F; Molnár, Z; Szele, F (2010)
We investigated the expression and role of the dopamine receptor 3 (D3R) in postnatal mouse subventricular zone (SVZ). In situ hybridization detected selective D3R mRNA expression in the SVZ. Fluorescence activated cell sorting (FACS) of adult SVZ subtypes using hGFAP-GFP and Dcx-GFP mice showed that transit amplifying progenitor cells and niche astrocytes expressed D3R whereas stem cell-like astrocytes and neuroblasts did not. To determine D3R's role in SVZ neurogenesis, we administered U-99194A, a D3R preferential antagonist, and bromodeoxyuridine in postnatal mice. In vivo D3R antagonism decreased the numbers of newborn neurons reaching the core and the periglomerular layer of the olfactory bulb. Moreover, it decreased progenitor cell proliferation but did not change the number of label-retaining (stem) cells, commensurate with its expression on transit amplifying progenitor cells but not SVZ stem cell-like astrocytes. Collectively, this study suggests that dopaminergic stimulation of D3R drives proliferation via rapidly amplifying progenitor cells to promote murine SVZ neurogenesis.